Protein S Thr103Asn Mutation Associated with Type II Deficiency Reproduced In Vitro and Functionally Characterised - Giri, Tusar Kanti; de Frutos, Pablo García; Dahlbäck, Björn (Thrombosis and Haemostasis, 2000)
Protein S functions as a cofactor to activated protein C (APC) in the degradation of FVa and FVIIIa. In protein S, the thrombin sensitive region (TSR) and the first EGF-like domain are important for expression of the APC cofactor activity. A naturally occurring Thr103Asn (T103N) mutation in the first EGF-like domain of protein S has been associated with functional (type II) protein S deficiency. To elucidate the functional consequences of the T103N mutation, recombinant protein S mutant was expressed in mammalian cells and functionally characterised. The expression level of protein S T103N from transiently transfected COS 1 cells was equal to that of wild type protein S. The mutant protein S and wild type protein S were also expressed in 293 cells after stable transfection, and the recombinant proteins purified. In APTT-and PT-based coagulation assays, the mutant protein demonstrated approximately 50% lower anticoagulant activity as compared to wild type protein S. The functional defect was further investigated in FVa-and FVIIIa-degradation assays. The functional defect of mutant protein S was attenuated at increasing concentrations of APC. The results demonstrate the region around residue 103 of protein S to be of functional importance, possibly through a direct interaction with APC.
Keywords: Anticoagulant protein S; functional deficiency; natural mutation; in vitro reproduction